Ontolgy for Library Requirements Classification | ออนโทลโลจีการจําแนกความต้องการของผู้ใช้ในห้องสมุด - มีหนองหว้า, ไชย (PULINET Journal; Vol 2 No 3 (2558): กันยายน-ธันวาคม, 2015)
An ontology is an information descriptions. It uses to describe the user requirements in the library environment. According to the massive of the requirements, an hierarchy of requirements will help librarians understand and response in time. However, it is very difficult to find and meet the intelligent tools to capture those requirements and also information from the users will increase everyday usages which come from different ways. In this research, it introduces the method to capture, analysis and classify the requirements as “feedback concepts” from the library users.  Ontology approach is applied for Information classification and presents the understandable feedback as ontological framework in the XML tags format. Therefore, this framework could be used to monitor the library services and problems. The model of the requirements will be also represented as hierarchy structure which programmers use to develop the application for users monitoring systems in the resources managements.